19 Souls : Sin City Investigation #1 - Allen, J. D., 1966- (Woodbury, Minnesota : Midnight Ink, 2018)
Vegas PI Jim Bean is conned into leading a dangerous woman straight to her target.
Keywords: Private investigators -- Nevada -- Las Vegas -- Fiction; Mystery fiction